‘Pick-them-Up’, an Android Based Application to Shorten School Shuttle Time - Slamet Winardi; Tresna Maulana Fahrudin; Benediktus Anindito; Sri Wiwoho Mudjanarko (Future Science)
A school shuttle service required to arrive at the destination home on time for the students will not come late to school. However, the shuttle service often gets the incident delays to pick up the students, because the driver must wait for the students who were not ready at the previous pick up. There are many reasons that make those students unready to be picked up. For example, when the driver arrived they were still taking a bath, having their breakfast, getting dressed, and other reasons. The idea to create a mobile application which is able to shorten student shuttle time hoped to solve these problems, we called the application is ‘pick-them-up’. We designed the analysis of business process using Use Case and Activity Diagram, before we built the application. This application is installed on the android mobile phone for the parents, students and the shuttle driver. When the students are ready to be picked up, parents or students will press the ready button on the application. On the driver's screen application will appear the notification explain that the student is ready to be picked up. When the students will be back at their home, they will notice the location of the car through this application to make easier find the shuttle car service. The parents will also get a notification when the shuttle car service will start delivering the students at their home. This application does not only shorten the shuttle time and minimize student delays, but also make the students, parents, and driver more convenient. The test result of this application prototype achieved 100% of suitable features for the users.